Gender differences in the function of music for emotion regulation development in everyday life: An experience sampling method study - Ma’rof, Aini Azeqa; Zheng, Danhe; Zaremohzzabieh, Zeinab (Universiti Pendidikan Sultan Idris, 2023)
The present study employed experience sampling methodology (ESM) to examine the role of music in regulating emotions and the potential differences in music usage for emotion regulation between men and women in everyday life. The study spanned over seven days, including both weekdays and weekends, during which 28 participants (14 men and 14 women) were asked to complete a brief questionnaire 21 times a day. The questionnaire aimed to document instances of music listening in the past three hours, resulting in a total of 588 questionnaires being sent and 264 instances of music listening being analysed. Results indicate that listening to music in daily life may have a positive impact on emotion regulation and suggest possible differences in music usage between men and women for this purpose. The study's primary findings include: (1) Relaxation was the most commonly used strategy for regulating emotions with music; (2) Four primary mechanisms of music usage for emotion regulation, including emotion type, familiarity, and content of music, were found to be essential; (3) Listening to music was an effective emotion regulation strategy, particularly for regulating happiness and peacefulness; (4) Men were more likely to use music for active coping and to consider the type and content of music when selecting music; and (5) Music appeared to regulate the intensity of emotions similarly for both men and women, although men tended to report higher emotional intensity.